El bono demográfico y su incidencia en el crecimiento económico en Colombia durante el periodo 2000-2018 (2021)
The demographic bonus is known as the change in population structure, which allows the economically active population to surpass the economically dependent such as children and older adults, which is why the demographic bonus is taken as a positive factor when attracting benefits to a country, due to greater labor used to generate greater production and dynamism of the economy. The Colombian economy has had growth trends, thanks to important characteristics that make Colombia a country with high expectations, such as its large territory of fauna and flora, its agricultural diversity, its strong export products, such as coffee and roses, which allow obtaining high expectations about the country's growth, on the other hand, it has gone through conjunctural aspects, which reduce its growth and trend, such as the mortgage crisis in the United States or the international fall in oil prices, influential factors in the Colombian economy.